Evaluation of surgical scalpel versus semiconductor diode laser techniques in the management of gingival melanin hyperpigmentation: A split-mouth randomized clinical comparative study - Ganachari Bharath Chandra; Malleshappa Bhairammanavar Vinay Kumar; Narayan Narendra Walavalkar; Kharidhi Laxman Vandana; Pabbati Krishna Vardhan (Wolters Kluwer Medknow Publications, 2020)
Background: "Black gums" due to melanin pigmentation of the gingiva is one reason for the demand of cosmetic therapy. Clinicians are often faced with challenge to achieve gingival esthetics in such cases because of its recurrence. Although many procedures were described in literature for gingival depigmentation, only few are mentioning about the intensity of repigmentation. Hence, this study was designed to compare two different techniques for treatment of gingival melanin pigmentation. Materials and Methods: Twenty patients who were not esthetically pleased with the color of gingiva were selected. A randomized, split-mouth, depigmentation procedure was performed using surgical scalpel and diode laser techniques. Clinical parameters such as plaque and gingival index, bleeding, pain perception, wound healing, recurrence, and intensity of repigmentation were evaluated. Paired t-test and Chi-square test were used for analysis of data. Results: No bleeding was reported in patients treated with diode laser. Moderate pain was reported by patients treated with surgical scalpel, whereas none was reported in diode laser group. No statistically significant difference was observed for both treatment techniques in terms of wound healing, reappearance of gingival pigmentation, and intensity of the same at the end of 6 and 9 months postsurgically. Conclusion: Similar outcomes were observed for both the techniques. Few patients who resulted in no recurrence at 9 months were followed even up to 3 years. Hence, further studies should be done to know the underlying mechanisms. Keeping in mind of armamentarium and cost, surgical scalpel technique remained as the "gold standard" procedure for treatment of gingival melanin pigmentation.